Institutional ranking in a differentiated higher education in South Africa - Ntshoe, Isaac; Selesho, JM (South African Journal of Higher Education, 2016)
Ranking institutions on a league table style is explicitly or implicitly used by agencies to determine excellence and performance and reputation of institutions. However, there is a growing concern that this tool tends to encourage drifts of missions, foci, purposes and specialisations of knowledge and skills produced by different higher education institutions globally. This article takes issue with the widely accepted practice of institutional ranking on league table style drawing examples from South Africa. It begins by describing inherent drawbacks of league table approaches and proposes alternative forms of determining performances of institutions. This is followed by discussions on South Africa highlighting the challenges of league table styles to rank institutions in systems where institutions are differentiated in terms of purposes and missions, and how it might subtly encourage mission drift. The third section is devoted to discussions and conclusion.